Head, neck & dental anatomy - Short, Marjorie J., 1935-; Levin-Goldstein, Deborah (Clifton Park, NY : Delmar Pub., 2013)
HEAD, NECK and DENTAL ANATOMY, 4E, International Edition is brimming with new, full-color figures that showcase anatomical details of the mouth and teeth. The most important features of each tooth are detailed in brief charts, making excellent study guides. Known for its engaging style, this concise resource is fully revised, including new worksheets with multiple choice and labeling questions. With its enhanced figures, fresh design, and updated materials the fourth edition promises to be a reliable go-to resource throughout your education and career
pt. I. Introduction to the oral cavity -- Nomenclature -- Structure of the oral cavity -- The tooth and its surrounding structures -- Tooth identification systems -- pt. II. Permanent anterior teeth -- Maxillary incisors -- Mandibular incisors -- Canines -- pt. III. Permanent posterior teeth -- Maxillary premolars -- Mandibular premolars -- Maxillary first and second molars -- Mandibular first and second molars -- Third molars -- pt. IV. Related topics -- Primary dentition -- Tooth development -- Occlusion -- Form and function -- pt. V. Head and neck anatomy -- Osteology of the skull -- Muscles of the head and neck -- Nerves of the head and neck -- Arteries of the head and neck -- Salivary glands -- Temporomandibular joint.
Title from cover
dental bookfair2015
Includes bibliographical references (p. 303-304) and index.
Keywords: Head -- Anatomy; Neck -- Anatomy; Mouth -- Anatomy; Teeth -- Anatomy